Desarrollo de un prototipo de tarjeta electrónica para la aplicación en alarmas comunitarias. - Toral Escobar, Lino Andrés (2022)
With an alarm system creation is sought to help and benefit the different Latacunga neighborhoods, due to the insecurity high rate that is going through the country, in general, for some reason, it arises the need of proposing the electronic card prototypes design, which go to be used for a security system. The project has two electronic card prototypes; the first is an emergency button that is charged of emitting the on and off signal, which is sent to the second prototype, this first prototype has a 3.7 V lipo battery, whose is rechargeable for ensuring that this device is wireless and it can be activated from anywhere, which it is needed; the second prototype is the actuator, this electronic card will be charged of receiving the emergency button activation and deactivation signal, this prototype will be powered by a 110 VAC source and has an output to connect a siren, which it is powered by the same source. Both prototypes have a microcontroller, whose has a built-in Wi-Fi module that allows better communication between devices by not depending about cables and therefore, it increases the operating distance between the cards, thereby increasing reliability and useful life for alarming systems.